Nurses' knowledge and practice towards prevention of surgical site infection / Fatimah Sham ... [et al.] - Sham, Fatimah; Abdul Raji, Nur Azira; Omar, Mohd Fitri; Hasan, Zulkarnain; Patahorahman, Muhammad Khairi; Mohamed Sihat, Hapesah; Supramaaniam, Yogarani (Universiti Teknologi MARA Cawangan Sarawak, 2021)
Surgical Site Infection (SIS) is a common healthcare-associated infection that significantly impacts patient safety and financial losses for health systems. Enhancing nurses' knowledge and practice is an essential component in the prevention of the spread of infection. The study aims to assess the knowledge and practice of preventing surgical site infection among nurses. A cross-sectional study was conducted among 306 nurses in two public hospitals in Malaysia. Data were obtained from selfadministered questionnaires and analyzed using the IBM Statistical Packages for Social Science (SPSS) Window Version 23. This study revealed that 85.3 % of nurses had good knowledge, and 97.7 % had good practice regarding SSI prevention. However, there was no significant difference between the nurses' knowledge and practice towards Prevention SSI (x2: 1.10; p-value: 0.28). There was a statistically significant association between working unit